P124 Differences in OSA pathophysiological traits between mandibular advancement therapy responders versus non-responses and the influence of obesity. (9th November 2022) - Tong, B; Chiang, A; Naik, G; Osman, A; Bull, C; Donegan, M; Pinczel, A; Rawson, G; Pitcher, G; Brown, E; Kwan, B; Mukherjee, S; et al.
Abstract: Mandibular advancement therapy (MAS) is a recognised second-line therapy for obstructive sleep apnoea (OSA). However, MAS treatment outcomes vary and are difficult to predict. Recent studies have investigated the role of OSA endotypes to predict MAS therapy outcomes. However, whether OSA endotype predictors differ between obese and non-obese people with OSA is unknown. Thus, this study aimed to compare OSA endotypes between responders and non-responders to MAS therapy in obese and non-obese individuals. 90 people with OSA (AHI>10events/h) were studied. OSA was confirmed via in-laboratory polysomnography. A detailed physiology night was subsequently performed prior to MAS therapy. OSA endotypes were estimated from the detailed physiology polysomnography using a custom-designed, validated, semiautomated script. OSA endotypes were compared between responders (residual AHI<10events/h) and non-responders to MAS therapy. Further comparisons were made between obese and non-obese groups. Responders to MAS therapy had a less collapsible upper airway; Vpassive: 93[88, 96]vs.85[62, 94]%Veupnea, p=0.003); Vactive: 103[95, 112]vs.98[16, 104] %Veupnea, p=0.008), better pharyngeal muscle compensation Vcomp: 9.8[4.3, 19.6]vs.3.3[-19.1, 18.6]%Veupnea, p=0.02), lower arousal threshold (114[109, 144]vs. 142 [117, 177]%Veupnea, p=0.006) and tended to also have lower loop gain (0.48 ±0.1vs. 0.42±0.1, p=0.05). . These findings were similar in obese versus non-obese individuals although loop gain was significantly lower in responders versus non-responders in the non-obese (p=0.01) but not the obese group (0.97). MAS therapy was most beneficial in people with a less collapsible upper airway, good pharyngeal muscle compensation, lower arousal threshold and loop gain at baseline. Prospective assessment of OSA endotypic traits may therefore help guide treatment decisions and improve MAS therapy outcomes.